Trinidad and Tobago : 2007 Article IV Consultation; Staff Report; Staff Statement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Trinidad and Tobago. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2008)
Trinidad and Tobago showed strong economic performance led by the buoyant energy sector. Executive Directors welcomed the robust economic activity, and the decline in public debt and external reserves. Directors stressed the need for strong macroeconomic and structural policies to enable the efficient absorption of energy revenues. They supported the tightening of fiscal policy and commended the monetary stance that has helped to contain inflation. They urged the authorities to improve the business environment and spur investment in the non-energy sectors and also encouraged plans to strengthen financial regulations and supervision.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet